Let us also do something to make learning and teaching more enjoyable! Pestalozzi Friday – The Hungarian professional development community of the international Pestalozzi Programme - Lázár, Ildikó (Autonomy and Responsibility Journal of Educational Sciences, 2022)
This study aims to present the story of the creation of the Budapest based Pestalozzi Friday professional development community as well as some of its most typical activities. The descriptions are supplemented by the analysis of the results of two small-scale surveys conducted among the participants. The fi rst survey shed light on the fact that although the principles of cooperative learning are considered essential at school, the majority of the participating teachers still rarely implement cooperative structures. The second survey conducted among the Pestalozzi Friday participants shows what prevents us teachers from creating similar professional development communities and from doing something together for more likeable schools. Becoming aware of our aims and diffi culties will hopefully help overcome the obstacles.